Radiation oncology primer and review : essential concepts and protocols - Rodrigues, George; Velker, Vikram; Best, Lara (Demos Medical Publishing, LLC., 2013)
The book describes the fundamental concepts, nomenclature and definitions of the field of radiation oncology. Divided into three sections Radiation Oncology Primer and Review covers the basic science, clinical science and technical and planning issues to give the trainee a full overview of the core knowledge base of the field. Co-written by a former radiation oncology residency program director and a team of radiation oncology residents, the book is organized in concise sections and is amply illustrated to highlight key points and help the reader understand and remember the major concepts discu.